Load Variation Effect on a Voltage Source Grid Connected Inverter for Solar Photovoltaic System - Taha, Amna; Sharief Fadul Babiker (University of Khartoum Engineering Journal, 2025)
Load variation effects on the stability and the power flow of a grid connected PV system. In this paper, a voltage source grid connected inverter (VSI) of 250 kW connected to a grid of 33 kV with a control unit capable of controlling a photovoltaic (PV) system on both DC and AC sides have been designed and simulated. The control unit is capable of performing maximum power point tracking technique (MPPT) and DC voltage regulation at the DC side. On the AC side, it controls the pulse width modulation (PWM), current regulation and the phase lock loop (PLL). The design has been performed by preparing the inputs, forming the mathematical equations and simulating them via MATLAB/Simulink package. Results showed that load variation does not affect the DC side of the PV system. Several changes has occurred on the AC side due to the load variation.